JP Morgan Chase and the London whale - Varma, Jayanth (London : SAGE Publications Ltd, 2017)
In April 2012, JP Morgan Chase & Company was struggling with large losses that had the potential to damage the reputation of the company, of its Chairman, Jamie Dimon, and of its Chief Investment Officer, Ina Drew. Both Dimon and Drew needed to respond quickly to the losses of early 2012 to protect their own careers and to safeguard the interests of the company.
Originally published: Varma, J. (2013). JP Morgan Chase and the London whale. F&A0505. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Dimon, Jamie; Drew, Ina; J.P. Morgan Chase & Co. -- History; Banks and banking -- Case studies; Organizational change -- Case studies; Strategic planning -- Case studies; Bank failures -- Case studies